Refractive Lenticule Extraction Complications. Issue 10 (October 2015) - Ramirez-Miranda, Arturo; Ramirez-Luquin, Tito; Navas, Alejandro; Graue-Hernandez, Enrique O.
Abstract : Purpose: To report the complications associated with refractive lenticule extraction (ReLEx) in its 2 modalities: femtosecond lenticule extraction (FLEx) and small incision lenticule extraction (SMILE). Methods: In this retrospective review of a consecutive clinical case series, all patients who had a complicated ReLex FLEx or ReLEx SMILE procedure at the Cornea and External Disease Department at the Instituto de Oftalmologia Fundacion Conde de Valenciana, Mexico City, Mexico, were included. Demographic characteristics, type of complication, and final refraction and visual outcomes were recorded. Results: Our study comprised 94 eyes in the FLEx group and 160 eyes in the SMILE group with a mean follow-up period of 36 months. In the FLEx group, 15 eyes (18.3%) presented surgery-related complications, including suction loss, black spots, bubbles in the interface, and lenticule misdissection. In the SMILE group, 43 eyes (26.9%) had complications, including an epithelial defect (the most frequent), suction loss, opaque bubble layer, cap rupture, and lenticule rupture. Conclusions: Although ReLEx complications can occur, most of them are related to inexperience and have a favorable resolution with no lasting effect on the patient's final visual acuity.